Understanding How Malaysian Women Appraise their Breast Cancer Symptoms: A Narrative Approach - Wan Mamat, Wan Hasliza; Lund, Susi; Jarrett, Nikki; Mohd Taib, Nur Aishah; Duke, Sue (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Awareness of breast cancer symptoms has made a positive impact on recognition and screening, however there is little research describing how women interpret their bodily changes. This study was conducted to explore how Malaysian women with breast cancer appraise their symptoms and how their interpretation of the symptoms had been shaped by the social norms, knowledge and previous experiences. Materials and Methods: 14 women with breast cancer were recruited using purposeful sampling. The participants took part in in-depth, one-time, face-to-face, and audio-recorded interviews. All the interviews were subsequently transcribed verbatim and analysed using structure and content of a narrative approach. Results: Women interpreted their symptoms based on the physical presentation of the symptoms, previous experiences, and societal norms and beliefs. Some women immediately understood the potential meaning of their breast changes and sought medical opinion, while others waited from one week up to until one year to observe symptoms or normalised them in terms of previous and current experiences. The use of narrative enabled these women to recapitulate particular experiences that had special meaning in order to make sense of their action. Conclusions: The way women interpreted their symptoms reflected their understanding on the significant meaning of the symptoms. Acknowledging this symptom appraisal information may assist healthcare professionals in providing appropriate information that can challenge misconceptions, myths, and negative beliefs about breast cancer to improve breast cancer awareness and early detection among the community.